2015
DOI: 10.1007/s11356-015-4627-z
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of polybrominated diphenyl ethers and polychlorinated biphenyls in the indoor dust of e-waste recycling facilities in South Africa: implications for occupational exposure

Abstract: Workplace exposure to persistent organic pollutants is a concern for human health. This study examined the presence of polybrominated diphenyl ethers (PBDEs) and polychlorinated biphenyls (PCBs) in the indoor dust from two major e-waste recycling sites and a university electronic equipment repair workshop in Durban, South Africa, in order to evaluate the implication of dust for occupational exposure. The mean ∑(n = 8)PBDEs and ∑(n = 3)PCBs were 20,094 and 235 ng g(-1), respectively. The levels of PBDEs and PCB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 42 publications
1
11
2
Order By: Relevance
“…They also exceed those in other previous studies, (Tue et al, 2013;Tan et al, 2007;Ali et al, 2012) reported PCBs in Vietnamese homes around e-waste sites; Singaporean, Kuwaiti, and Pakistani homes respectively; but are lower than those reported by Abafe andMartincigh, 2015 andZheng et al, 2015 for South African offices and homes around e-waste handling sites respectively. Worthy of note is the similar congener profile in our report to the other two reports on PCBs in dust from African countries (Harrad et al, 2016;Abafe and Martincigh, 2015) (Table 2). This may imply that the PCB formulations used in Nigeria and South Africa are similarly dominated by higher chlorinated congeners (Harrad et al, 2009) such as Aroclor 1260.…”
Section: Comparison Of Concentrations Obtained In Soil and Dust With contrasting
confidence: 64%
See 1 more Smart Citation
“…They also exceed those in other previous studies, (Tue et al, 2013;Tan et al, 2007;Ali et al, 2012) reported PCBs in Vietnamese homes around e-waste sites; Singaporean, Kuwaiti, and Pakistani homes respectively; but are lower than those reported by Abafe andMartincigh, 2015 andZheng et al, 2015 for South African offices and homes around e-waste handling sites respectively. Worthy of note is the similar congener profile in our report to the other two reports on PCBs in dust from African countries (Harrad et al, 2016;Abafe and Martincigh, 2015) (Table 2). This may imply that the PCB formulations used in Nigeria and South Africa are similarly dominated by higher chlorinated congeners (Harrad et al, 2009) such as Aroclor 1260.…”
Section: Comparison Of Concentrations Obtained In Soil and Dust With contrasting
confidence: 64%
“…To the best of our knowledge, there are only two reports of PCB concentrations in indoor dust in Africa. Firstly, Abafe et al, 2015 measured concentrations of three PCB congeners (PCB 28,153,and 180) in indoor dust samples from ten homes, eleven offices, and thirteen computer laboratories in Durban, South Africa. The second report measured six indicator PCBs in dust samples from three microenvironment categories (homes, cars and offices) in Nigeria (Harrad et al, 2016).…”
Section: Folarin Et Al 2018 Page 3 Of 23mentioning
confidence: 99%
“…Similarly, Isimekhai et al [93] reported high levels of metals at the e-waste recycling site in Nigeria; the levels of copper (329 to 7106 mg kg −1 ), lead (115 to 9623 mg kg −1 ), and zinc (508 to 8178 mg kg −1 ) were consistently Pakistan [27,39] Philippines [91,113] South Africa [114] Uruguay [115] Vietnam [113] Physical dismantling using bare hands and simple hand tools such as hammers, chisels screw drivers to separate different material *From a number of workshops; GM: geometric mean.…”
Section: Metals/metalloids Contamination In Different Environmental Cmentioning
confidence: 97%
“…Soil samples collected from the acid leaching area in an informal recycling site in Guiyu were also found to contain high levels of antimony, cadmium, copper, lead, nickel, tin, and zinc [88]. The detection Pakistan [27,39] Philippines [91,113] South Africa [114] Uruguay [115] Vietnam [113] Physical dismantling using bare hands and simple hand tools such as hammers, chisels screw drivers to separate different material of the less common contaminants (antimony and tin) at levels higher than the principal contaminants suggests the need to take into account other chemical constituents of EEE. Elevated levels of cadmium, lead, Mercury, and zinc are still being detected in soil in Ziya, northern China, where informal e-waste recycling ceased in 2011 [89], highlighting the legacy of non-biodegradable and persistent pollutants and the need for the clean-up of historical e-waste recycling sites.…”
Section: Metals/metalloids Contamination In Different Environmental Cmentioning
confidence: 99%